2021
DOI: 10.1111/ejn.15315
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory enhancement of overt behavior requires multisensory experience

Abstract: The brain has evolved an ability to integrate information across multiple sensory systems, thereby enhancing the probability of survival in a wide variety of environments (Stein & Meredith, 1993). One of the best-studied neural models used to examine this phenomenon is the visual-auditory neuron in the superior colliculus (SC). These midbrain neurons can integrate signals transduced from spatiotemporally congruent visual and auditory stimuli (e.g., stimuli derived from the same events) to significantly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…These results are seemingly at odds with studies in dark reared cats in which no multisensory enhancement was found in multisensory neurons of the superior colliculus ( Wallace et al., 2004 ; Yu et al., 2019 ). Recently, however, multisensory gains in superior colliculus neurons have been observed when the animals were tested in light rather than in the dark ( Smyre et al., 2021 ). We conducted our experiment in a lit room and, moreover, unlike the previously tested dark-reared cats, the CC individuals of the present study had extensive experience with audio-visual stimuli in natural environments after cataract-removal surgery, many for several years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are seemingly at odds with studies in dark reared cats in which no multisensory enhancement was found in multisensory neurons of the superior colliculus ( Wallace et al., 2004 ; Yu et al., 2019 ). Recently, however, multisensory gains in superior colliculus neurons have been observed when the animals were tested in light rather than in the dark ( Smyre et al., 2021 ). We conducted our experiment in a lit room and, moreover, unlike the previously tested dark-reared cats, the CC individuals of the present study had extensive experience with audio-visual stimuli in natural environments after cataract-removal surgery, many for several years.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory experiences made during sensitive periods of development have a strong and lasting impact on how information from the different sensory systems is combined ( Putzar et al., 2007 ; Schorr et al., 2005 ; Smyre et al., 2021 ; Sourav et al., 2019 ; Wallace and Stein, 2007 ). For example, neuroanatomical and neurophysiological studies in owls have revealed distinct neural mechanisms for crossmodal recalibration depending on the age of the animals: Although crossmodal recalibration in juvenile owls was mediated by anatomical changes ( DeBello et al., 2001 ; Feldman and Knudsen, 1997 ), it was associated with top-down guided physiological changes in adult animals ( Hyde and Knudsen, 2002 ; Knudsen, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lower ALFF in parietal cortex in the CC compared with the SC group might indicate a lower visual influence on multisensory (spatial) processing. Recently, Smyre et al 101 reported an impaired multisensory detection and localization in dark reared cats. In fact, two behavioural studies have found a reduced visual impact on tactile spatial performance in congenital cataract-reversal individuals with a history of longer lasting visual deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Multisensory response enhancement (ME SF ) was calculated as the percent difference between the mean multisensory and most effective unisensory response calculated on a trial-by-trial basis via bootstrap, a metric referred to as “statistical facilitation” (SF) ( Miller, 1982 ; Otto et al, 2013 ; Nava et al, 2014 ; Wang et al, 2020 ; Smyre et al, 2021 ; Bean et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%